Analisis Waktu Standar Produksi dengan Stopwatch Time Study Guna Penentuan Jumlah Tenaga Kerja - Alfan, Alfan Ridho; Putri, Erni Puspanantasari (SURYA TEKNIKA, 2025)
UD Logam Abadi is a manufacturing company that produces accessories for PLN and Telkom, one of which is the Suspensen Q spare part. The company is experiencing difficulties due to the lack of a standard working time, resulting in workers not having daily targets, which impacts the achievement of production volume. Fluctuating market demand and the manual assembly process make the role of labor very important. This research aims to determine the standard production time and the optimal number of workers using the Stopwatch Time Study method. The research results indicate that the standard time to complete one unit of Suspensen Q is 550.49 seconds or about 9.16 minutes. The optimal number of workers needed is 2 to 3 per division.